Intra‐specific kin recognition contributes to inter‐specific allelopathy: A case study of allelopathic rice interference with paddy weeds. (28th May 2021) - Xu, You; Cheng, Hui‐Fang; Kong, Chui‐Hua; Meiners, Scott J.
Summary: Species interactions and mechanisms affect plant coexistence and community assembly. Despite increasing knowledge of kin recognition and allelopathy in regulating inter‐specific and intra‐specific interactions among plants, little is known about whether kin recognition mediates allelopathic interference. We used allelopathic rice cultivars with the ability for kin recognition grown in kin versus non‐kin mixtures to determine their impacts on paddy weeds in field trials and a series of controlled experiments. We experimentally tested potential mechanisms of the interaction via altered root behaviour, allelochemical production and resource partitioning in the dominant weed competitor, as well as soil microbial communities. We consistently found that the establishment and growth of paddy weeds were more inhibited by kin mixtures compared to non‐kin mixtures. The effect was driven by kin recognition that induced changes in root placement, altered weed carbon and nitrogen partitioning, but was associated with similar soil microbial communities. Importantly, genetic relatedness enhanced the production of intrusive roots towards weeds and reduced the production of rice allelochemicals. These findings suggest that relatedness allows allelopathic plants to discriminate their neighbouring collaborators (kin) or competitors and adjust their growth, competitiveness and chemical defense accordingly. Abstract : This study identified the role of kin recognition in mediating allelopathic rice interference with weeds, and addressed an interesting concept that relatedness allows allelopathic plants to discriminate neighbouring collaborators or competitors and adjust growth, competitiveness and chemical defense accordingly.